Biocompatibility and microscopic evaluation of polyurethane–poly(methyl methacrylate)–titnanium dioxide based composites for dental applications. Issue 3 (31st August 2013) - Zuber, Mohammad; Tabasum, Shazia; Jamil, Tahir; Shahid, Muhammad; Hussain, Rizwan; Feras, Khalid Sajjad; Bhatti, Khalid Pervez
ABSTRACT We prepared and then blended polyurethanes (PUs) with poly(methyl methacrylate)s (PMMAs) and TiO2 by varying the percentage compositions to form pellets. The chemistry of all of the blended samples was confirmed by Fourier transform infrared spectroscopy. The incorporation of TiO2 into the PU–PMMA matrix was confirmed with scanning electron microscopy analysis. Differential scanning calorimetry analysis and compression testing was performed, and the results are discussed. The cytotoxicity level of the prepared blends displayed dependence on the composition ratio of the PU–PMMA blends. The results reveal that the optimum PU contents in the PU–PMMA–TiO2 blend were responsible for its better biocompatibility. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39806.